Eksistensi Badan Usaha Milik Desa (Bumdes) Dalam Pembangunan Ekonomi Di Desa - I Wayan Sutrisna (Jurnal Ilmiah Cakrawarti, 2020)
The development carried out in the village is currently undergoing increasingly rapid changes, so that village government officials are needed who can really adapt to chang- ing conditions. The village government must also be able to explore the potential of the vil- lage which can be used to increase Village Original Income (PAD), which leads to improving the welfare of all village communities. Community empowerment is absolutely necessary so that society becomes strong, especially in the economic field. Community empowerment is absolutely necessary so that society becomes strong, especially in the economic field. Village Owned Enterprises (BUMDes) is an economic empowerment institution for rural commu- nities, this institution is a forum for village communities to strengthen the economy towards prosperity. It is hoped that the government will continue to strive to provide understanding to the village government of the importance of the existence of this economic institution in empowering village communities. Strengthening BUMDes institutions must be a priority by the village government, supported by all levels of society. Well-managed village business institutions will provide enormous benefits to the life of village communities. The community will receive benefits individually, especially those who are directly involved in this village business. In addition, BUMDes that are well managed will be able to increase village govern- ment finances used in village development to reduce poverty and at the same time improve community welfare. This paper uses a study with a literature study approach which aims to find out about the existence of BUMDes in Economic Development in Villages.